A new distance measure for free text keystroke authentication - Davoudi, H.; Kabir, E. (2009 14th International CSI Computer Conference, 2009)
Keystroke dynamics-based authentication, KDA, verifies users via their typing patterns. To authenticate users based on their typing samples, it is required to find out the resemblance of a typing sample and the training samples of a user regardless of the text typed. In this paper, a measure is proposed to find the distance between a typing sample and a set of samples of a user. For each digraph, histogram-based density estimation is used to find the pdf of its duration time. This measure is combined with another measure which is based on the two samples distances. Experimental results show considerable decrease in FAR while FRR remains constant.